The Joy of Working – Is Your Environment Star Studded? What is a Star Studded Environment? - Shewchuk, Muriel (Operating Room Nurses Association of Canada Journal, 2005)
A star studded Perioperative professional department is everyone’s dream. The anticipation of arriving at work greeted by enthusiastic, knowledgeable experts who demonstrate initiative, positive attitudes and humour are “just what the doctor ordered”. At the end of the day you return home enriched, excited and rewarded, even if exhausted, and look forward to what you will contribute and learn the next day. The professional colleagues you encounter are patient care experts, mentors, role models, friends and team players. These are the Perioperative stars dreams are made of. It’s up to you to hang your personal star in the environment and help those around you rise to the occasion and let everyone be a star!